2009
DOI: 10.1038/bmt.2008.417
|View full text |Cite
|
Sign up to set email alerts
|

Intra-BM injection to enhance engraftment after myeloablative umbilical cord blood transplantation with two partially HLA-matched units

Abstract: The time to neutrophil engraftment for adult patients after myeloablative double unit umbilical cord blood (UCB) transplantation is 23 days when the two units are given i.v. We hypothesized that the intra-BM injection (IBMI) of one of the two UCB units would reduce systemic loss of hematopoietic progenitors and shorten time to neutrophil recovery after myeloablation. Ten patients with a median age of 35 years were transplanted. The unit to be given by IBMI was randomly assigned; the other unit was given i.v. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 24 publications
3
75
0
1
Order By: Relevance
“…[7][8][9][10] Proposed solutions include direct inoculation of UCB cells into the bone marrow to overcome ineffective UCB cell homing, 12,38,39 and increasing the effective number through the combination of several cord units 11,12 and ex vivo expansion of progenitors. [13][14][15] In addition to generation of a progenitor-enriched graft by functional-negative selection (as compared with phenotypic identification), pretransplant exposure to the death ligands enhanced progenitor activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] Proposed solutions include direct inoculation of UCB cells into the bone marrow to overcome ineffective UCB cell homing, 12,38,39 and increasing the effective number through the combination of several cord units 11,12 and ex vivo expansion of progenitors. [13][14][15] In addition to generation of a progenitor-enriched graft by functional-negative selection (as compared with phenotypic identification), pretransplant exposure to the death ligands enhanced progenitor activity.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The use of UCB for transplantation is limited by the insufficient cell numbers required to attain the threshold of adult recipients and the slow tempo of engraftment. [7][8][9][10] Approaches to overcome the small cell numbers have been implemented with relative success, including transplantation of two or more UCB units 11,12 and ex vivo expansion of progenitors. [13][14][15] The second limitation of UCB transplants is a relatively slow tempo of reconstitution, which is likely an intrinsic characteristic of circulating primitive progenitors inexperienced in interaction with the bone-marrow stroma.…”
Section: Introductionmentioning
confidence: 99%
“…Frassoni et al 25 reported on the IBMI in the setting of UCB transplantation with one unit, whereas our group studied this technique in the setting of two UCB units. 24,25 Frassoni et al 25 observed consistent engraftment and a reduced incidence of acute GVHD, but all patients received anti-thymocyte globulin, which may have favorably influenced the risks of GVHD. Nevertheless, considering the cell doses infused, their results with this IBMI approach were encouraging.…”
Section: Ucb Transplantation In Adults With Malignanciesmentioning
confidence: 99%
“…Recently reported studies have investigated the intra-BM injection (IBMI) of UCB grafts. 24,25 The rationale for these studies was to enhance neutrophil recovery by delivering the HSCs directly into the BM space, thus reducing the systemic 'wasting' of an already limited number of progenitors. Frassoni et al 25 reported on the IBMI in the setting of UCB transplantation with one unit, whereas our group studied this technique in the setting of two UCB units.…”
Section: Ucb Transplantation In Adults With Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation